Study of modelling, analysis and testing of droop control for converter-connected generation in autonomous microgrids - Yong, Xun Jie (Nanyang Technological University, 2021)
Droop control is essential for sharing demand power between generators in autonomous microgrids where the electricity distribution grid provides no assistance. Droop control is essential for sharing demand power between generators in autonomous microgrids where the electricity distribution grid provides no assistance. Since proportional load sharing may not be feasible in many cases of inverter-based microgrids, droop control plays a significant role in the microgrid frequency regulation sector. With the large-scale use of renewable energy sources, the conventional method of incorporating these renewable energy sources as grid following units has been shown to cause frequency instability in the current power system, which is increasingly evolving from a synchronous machine-based system to an inverter-dominated system. Many researchers have suggested that virtual inertia control algorithms be used to make virtual inertia generators behave as synchronous generators to the grid, thus preserving and improving system stability. Different load types and droop coefficients are investigated and evaluated in this report to assess the efficiency of the droop control. Through a study of the literature and simulation studies, it was discovered that if inertia and droop control can work in concert, the system's stability can be increased while the cost of storage is reduced. The suitability of a particular load type is determined by the degree of detail needed and the system control design used in the replication of synchronous generator dynamics.